Associations between Depression, Employment, and Relationship Status During the Transition into the Workforce: A Gendered Phenomenon? - Domene, José F.; Arim, Rubab G. (Canadian Journal of Counselling and Psychotherapy, 2016)
This study involved an examination of the associations among self-reported depressive symptoms, two aspects of quality of employment, and romantic relationship status in emerging adults transitioning into the workforce. Hierarchical multiple regression analyses were conducted on a sample of 586 men and 518 women drawn from the Canadian National Longitudinal Survey of Children and Youth. The analyses revealed that employment satisfaction is negatively associated with depressive symptoms, with the strength of association being stronger for women than men. In contrast, no significant associations were found for being employed in a position that was consistent with one’s aspirations or romantic relationship status.